Electric Scooter (EZ Vroom) - Asril Rajo Mantari, Muhammad Hanafi (Multidisciplinary Applied Research and Innovation, 2023)
The focus of this project is to design and fabricate a prototype of an electric scooter named as EZ Vroom. EZ Vroom was designed for the purpose of facilitating commuting to and from campus for University Tun Hussein on Malaysia (UTHM) students. The design and fabrication of EZ Vroom aims to simplify student life on campus by making rentals accessible to UTHM students. Students are therefore highly recommended to use electric scooters presently as it is very simple to handle, does not require driving licence and also fuel (just only need to charge the battery). According to the scope of project, the maximum speed of this electric scooter is 45 km/h, and there is only one person allowed to ride on it. Further, this electric scooter is fairly lightweight and also convenient to carry along with the battery can be fully charged in a maximum of one hour of time. The EZ Vroom fabrication process also involves a lot of mechanical and fundamental electrical knowledge. It can be seen in the beginning phases of sketching and designing the Ez Vroom using the Computer-Aided Design application known as SOLIDWORKS, progressing on to the fabrication of the EZ Vroom frame, and completing with the wiring of the electrical components. The overall price for the development of this electric scooter is therefore RM 600.00. A survey for UTHM students related to the rental of EZ Vroom has been conducted throughout this project. Numerous tests, including toughness and velocity tests, have been passed by EZ VRoom to demonstrate its capabilities. The analysis shows that Ez Vroom is a great choice for students to safely get themselves to university. However, a few issues came up during the fabrication process, preventing the controller and the break from being installed on the EZ Vroom.